Modern PHP new features and good practices - Lockhart, Josh (O'Reilly Media, 2015)
With this practical guide, you'll learn how PHP has become a full-featured, mature language with object-orientation, namespaces, and a growing collection of reusable component libraries. You'll learn best practices for application architecture and planning, databases, security, testing, debugging, and deployment.